Islamic Economic System: Scientific Method Versus Aqliyah Method - Al Mahdi; Andriyani Andriyani; Fitra Mulyawan; Rahma Dani; Kiki Yulinda; Dora Tiara (Journal of Islamic Economics and Finance Studies, 2025)
This research discusses two main approaches in the development of Islamic economics, namely the scientific method and the rational method. The scientific method is an empirical approach that emphasizes observation, experimentation, and data analysis in testing economic phenomena objectively and systematically. In contrast, the rational method is a rational approach that focuses on the ability of reason to understand the principles and fundamental values of Islamic economics sourced from the Qur'an and Hadith. The research method used in this study is library research with secondary data sources. This study aims to show that these two methods are not contradictory approaches, but rather complementary in building a comprehensive epistemology of Islamic economics. Through literature study and analysis of academic literature, it was found that the scientific method is very effective in measuring the application of Islamic values in modern economic practices, while the rational method plays an important role in formulating the philosophical and normative principles of Islamic economics. The integration of both becomes important in creating an Islamic economic system that is not only rational and empirical but also value-oriented and based on revelation. Thus, Islamic economics can develop as a distinct discipline, different from conventional economics in terms of goals, approaches, and fundamental values.